Novel Design of Power Generation Using Windmill in Integration with Biomass Energy System (International Journal of Innovative Research in Engineering & Management, 2021)
More than two billion people living in underdeveloped  countries, the bulk of whom reside in rural areas, do not have  access to electricity. Kerosene and animal dung are used to  provide many of the region's energy needs in addition to  traditional and non-electric energy sources, such as human and  animal muscle power. There has been a rise in recent years in  environmental concerns due to fossil fuel consumption and the  global warming phenomenon. For these reasons, renewable  energy hybrids have been proposed as a possible option. Wind  energy is supposed to contribute to the global state of the  environment because of its purity. Also, every year, metric tons  of residential garbage is collected, mostly being dumped in  spread areas. In India, paper and plastic make up the majority  of municipal solid waste (MSW), accounting for 80 percent of  total MSW. Using anaerobic digestion or direct combustion,  the waste of the municipality can be transformed into power for  use. Employing a windmill to power a biomass generator is the  topic of this paper. For a windmill that operates on an  intermittent basis, a sufficient number of battery banks are  installed. Biomass and windmills are used to generate  electricity, and a battery bank can also be employed to store  excessive and deficit power. All of the biomass generator's  operations can be scheduled to save on costs. As part of this  article, a compact wind farm with biomass energy and a battery  backup is described. Proficient assessments of a wind-bio  energy hybrid power plant with an output of 6 kW are provided.  The paper's goal is to determine the feasibility of the system  and optimize it.
Keywords: Windmill; Biomass; Fossil energy; Hybrid; Energy; Municipal; Solid waste